Nanocellulose as a colorimetric biosensor for effective and facile detection of human neutrophil elastase. (15th July 2019) - Ling, Zhe; Xu, Feng; Edwards, J. Vincent; Prevost, Nicolette T.; Nam, Sunghyun; Condon, Brian D.; French, Alfred D.
Highlights: Cotton cellulose nanocrystals were fabricated by deep eutectic solvents treatment. Biosensors were designed with protease sensitive peptide on DCNC/WCNF to detect HNE. DCNC had better biosensitivity due to larger crystalline size and less carboxyls. Immobilization of peptides took place mainly on (110) lattice plane of nanocellulose. The biosensors are reliable for chronic wound dressing. Abstract: Nanocellulose has functionalities suitable for efficient sensor transducer surface design including crystallinity, biocompatible and high specific surface area. Here we explore two forms of nanocellulose as transducer surfaces to enable colorimetric detection of human neutrophil elastase (HNE), and a wide range of inflammatory diseases. A deep eutectic solvent (DES) was utilized to mediate formation of cotton cellulose nanocrystals (DCNCs) employed to prepare a peptide-cellulose conjugate as a protease sensor of HNE. The tetrapeptide-cellulose analog on DCNC is contrasted with an analogous derivative of TEMPO-oxidized wood cellulose nanofibrils (WCNFs). DCNCs showed greater degree of substitution of HNE tetrapeptide and sensitivity to the elastase than WCNFs, despite the smaller surface area and pore sizes. XRD models revealed the higher crystallinity and larger crystallite sizes of DCNCs, indicating the well-arranged cellulose chains for immobilization of the tetrapeptide on (110) lattice reflections of cellulose crystals. The sensitivity of DCNCs-based colorimetric sensor was less than 0.005 U/mL, which would provide a convenient, sensitive sensor applicable for improved colorimetric point of care protease biomarker detection.